Description and Pathogenicity of Colletotrichum Species Causing Chili Anthracnose in Yogyakarta, Indonesia - Rosa Chryse Sutomo; Siti Subandiyah; Arif Wibowo; Ani Widiastuti (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2022)
Chili anthracnose caused by Colletotrichum spp. is a significant disease of chili cultivation in Indonesia. The current taxonomic status of Colletotrichum spp. has been rearranged due to a well-developed molecular study. Several species of Colletotrichum were re-identified after being analyzed by a polyphasic approach. The polyphasic method in this research combines morpho-cultural and molecular identification using ITS-rDNA and GADPH region. The pathogenicity test would be more reliable in identifying the species complexes of Colletotrichum that are difficult to differentiate. This study applies a polyphasic approach to identify Colletotrichum species causing chili anthracnose, especially in fruits collected from chili fields in Yogyakarta, Indonesia, and observe its pathogenicity in wounded and unwounded inoculation. The results of those combination methods showed that isolates collected from chili fields in Yogyakarta were C. scovillei. The pathogenicity test revealed that the fungus caused anthracnose disease in wounded and unwounded OR Twist 42 chili fruits. The unwounded infection was confirmed by amplification of the ChEC3 pathogenicity gene 24 h after inoculation, showing that appressoria production may possess an essential role in the unwounded inoculation. This study revealed that C. scovillei does not always need a wound for its pathogenicity